(untitled) (Experimental biology, 2015)
On structural parameters of kardio-respiratory system of animals adaptation to action exogene stresses-factors, and also dependence chronostability an organism of animals from a season of year is established. Daily and seasonal chronostructure parameters of biorhythms give the information on a functional condition of an organism.